UV inactivation of human infectious viruses at two full-scale wastewater treatment plants in Canada. (15th December 2018) - Qiu, Yuanyuan; Li, Qiaozhi; Lee, Bonita E.; Ruecker, Norma J.; Neumann, Norman F.; Ashbolt, Nicholas J.; Pang, Xiaoli
Abstract: Ultraviolet (UV) disinfection is widely used to inactivate microorganisms prior to release of treated municipal wastewater. However, limited data are available for in situ inactivation of infectious enteric viruses by UV treatment at full-scale. In this study, a total of 51 pre-UV and 50 post-UV samples were collected over a two-year period from two wastewater treatment plants (WWTPs) and analyzed for noroviruses, rotavirus, reovirus, sapovirus, astrovirus, enteroviruses, adenoviruses and JC virus. Both pre-UV and post-UV samples had relatively high concentrations of these viruses determined by qPCR. Infectious viruses were also observed in 98% of pre-UV samples and 76% of post-UV samples by cell culture, using either cytopathic effect (CPE) or integrated cell culture with qPCR (ICC-qPCR). Reovirus was the most common virus detected by ICC-qPCR, present in 92% of pre-UV and 48% of post-UV samples. Infectious enterovirus and adenovirus were detected by ICC-qPCR in 33% and 31% of pre-UV samples, 14% and 20% of post-UV samples, respectively. Mean log10 reduction estimates for infectious reovirus was 1.2 and 1.8 log for the two WWTPs as assessed by ICC-qPCR, which was similar to the reduction of total infectious viruses (1.5 and 1.7 log) as assessed by CPE in cells culture. Overall, quantification of infectious reovirus appears to provide a useful index of enteric virus inactivation during wastewater treatment at full-scale. To our knowledge, this is the first comprehensive study to assess UV inactivation of human enteric viruses at full-scale in WWTPs using both molecular and cell culture techniques, providing important information for quantitative microbial risk assessment of UV inactivation of human viruses in municipal wastewater. Graphical abstract: Highlights: Seven viruses were detected in both pre-UV and post-UV samples by qPCR with relatively high viral loads. Infectious viruses were more prevalent in pre-UV samples (98%) than post-UV samples (76%). Reovirus has the potential to act as a viral index during wastewater treatment. UV has certain effect on inactivation of infectious enterovirus and adenovirus in wastewater. Cell culture and ICC-qPCR can be used to assess UV inactivation of certain viruses, such as reovirus.